2003
DOI: 10.1385/bter:93:1-3:9
|View full text |Cite
|
Sign up to set email alerts
|

Copper, Zinc, and Selenium in Whole Blood and Thyroid Tissue of People with Various Thyroid Diseases

Abstract: We investigated the possible differences among the concentrations of copper, zinc, and selenium, and their mutual relations in the whole blood and thyroid tissue of patients with various thyroid disorders. Trace elements were determined by total-reflection X-ray fluorescence. The mean levels of these metals in blood as well as the mean Cu/Zn, Cu/Se, and Zn/Se ratios in the patients with thyroid cancer were significantly higher that in other patients and the control groups. However, the mean Zn and Se concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
59
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 33 publications
5
59
0
3
Order By: Relevance
“…Other authors have estimated the concentration rates of Cu/Zn in the cancerous thyroid tumor were significantly higher than in the normal and other thyroid diseases. 16,17 This study also confirmed that the cancerous thyroid tissues have higher Cu concentrations than the non-cancerous (adenoma) thyroid…”
Section: Determination Of Copper and Zinc In Human Thyroid Tissuessupporting
confidence: 69%
See 1 more Smart Citation
“…Other authors have estimated the concentration rates of Cu/Zn in the cancerous thyroid tumor were significantly higher than in the normal and other thyroid diseases. 16,17 This study also confirmed that the cancerous thyroid tissues have higher Cu concentrations than the non-cancerous (adenoma) thyroid…”
Section: Determination Of Copper and Zinc In Human Thyroid Tissuessupporting
confidence: 69%
“…Similarly, Kucharzewski et al have observed the lower Zn concentrations in the cancerous thyroid patients than in the other thyroid patients. 17 In another study, 15 Zn concentrations of cancerous and adenoma thyroid tissues were found to be close to each other. We estimated that the concentrations rates of Cu/Zn in cancerous thyroid tissues were significantly higher (p < 0.05) than in the non-cancerous tissues ( Table 2).…”
mentioning
confidence: 83%
“…Moreover, zinc levels measurements in thyroid tissue together with oxidant/antioxidant balance evaluation could also be of assistance in explaining the mechanism. 27 Finally, thyroid nodules in patients with AITD should also be examined separately to assess the effect of zinc in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Serum Se concentrations do not reflect tissue levels (Kucharzewski et al 2002(Kucharzewski et al , 2003. In fact, intake of a single 200 mg dose of Se can produce adequate serum levels in AIT patients, as in normal individuals (Duntas et al 2003).…”
Section: Introductionmentioning
confidence: 99%